HuangLian-4 alleviates myocardial ischemia-reperfusion injury by activating the pro-survival STAT3 signaling pathway - Gong, Chelimuge; Wang, Dalintai; Zhang, Qingshan (Frontiers in Pharmacology, 2025)
Myocardial ischemia-reperfusion injury (MIRI) remains a major clinical challenge following revascularization for acute myocardial infarction. The multi-component, multi-target nature of traditional herbal formulas like HuangLian-4 (HL4) offers a promising therapeutic paradigm for this complex disease, yet its underlying molecular mechanism is poorly understood. This study aimed to systematically elucidate the cardioprotective mechanism of HL4 by integrating serum pharmacochemistry, network pharmacology, and systems biology with experimental validation. An in vitro MIRI model was established using a hypoxia/reoxygenation (H/R) protocol in H9c2 cardiomyocytes, and the effects of HL4 were assessed by ELISA, qRT-PCR, Western blot, and molecular docking. Our results demonstrate that HL4 treatment significantly attenuated H/R-induced cardiomyocyte injury and inflammation, reducing the release of CK-MB, LDH, IL-6, and TNF-α. Mechanistically, our primary finding revealed that HL4 markedly rescued the H/R-induced downregulation of the pro-survival factor STAT3 at both the mRNA and protein levels. This activation of STAT3 was accompanied by a significant increase in the anti-apoptotic protein Bcl-2 and a decrease in pro-apoptotic Bax, alongside the suppression of the maladaptive factor HIF-1α. These experimental findings were powerfully corroborated by systems-level bioinformatic analysis, which independently identified the STAT family as key upstream regulators of a MIRI-critical gene network. Furthermore, molecular docking confirmed a strong binding affinity between key active compounds of HL4 and the STAT3 protein. In conclusion, this study demonstrates that HL4 alleviates MIRI by activating the STAT3 signaling pathway, which in turn orchestrates a downstream anti-apoptotic program. Our findings provide a robust molecular rationale for the clinical use of HL4 and establish STAT3 modulation as a promising therapeutic strategy for MIRI.